News in Educational Technology - Miranda Ramón, Eva (1998)
At present, within the formation of Health Human Resources, three pedagogical models could be identified: transmission pedagogic that states ideas as well as knowledge are the most important topics regarding education, thus the student must receive what the "instructor", or the textbooks. Behavioral pedagogic with emphasizes in training, empirical and operative manifestations of knowledge, attitude and skill improvement. Finally, trouble pedagogic, which states that the student skill is the main point for social transformation in order to find out actual problems and seek for an original as well as creative solution. Thus, the ability that must be developed is to ask relevant inquiries in any case, to understand THE PROBLEM and be able to solve it properly. This model is based upon the constructive theory, where the student builds up his or her own knowledge, thus it is not important to lead him to repeat contents. According to this proposal we privilege this model in health; thus, throughout the use of the Bustos Operative Didactically Pattern, didactically tools were proposed to be applied through the formation of health staff. This model includes five steps: (1) Life experiences; (2) Reflection; (3) Documentation; (4) Application; and (5) Ampliation. The proposal does not include predetermined programs but the adjustment to institutional, local as well as national reality.